COVID-19 Testing Experience in a Resource-Limited Setting: The Use of Existing Facilities in Public Health Emergency Management - Assefa, Nega; Hassen, Jemal Yousuf; Admassu, Desalegn; Brhane, Mussie; Deressa, Mersen; Marami, Dadi; Teklemariam, Zelalem; Dessie, Yadeta; Oundo, Joseph (Frontiers in Public Health, 2021)
Introduction: Coronavirus disease 2019 (COVID-19) is a public health emergency with little testing and treatment experiences at its occurrence. Diagnostic and treatment rapidly changed in the world including Ethiopia. Haramaya University has strived to change its diagnostic capacity using existing facilities in response to the national call to the pandemic. Objective: This summary aims to detail experiences of setting up COVID-19 testing in Haramaya University laboratories, Eastern Ethiopia. Methods: Desktop exercise was conducted to understand the start-up and implementations of COVID-19 testing in two Haramaya University laboratories, Hararghe Health Research Partnership and Campylobacter Genomics and Environmental Enteric Dysfunction laboratories. Communication, formats, guidelines, and standards were reviewed and summarized. Discussion with those involved in the start-up and implementation of the testing were also held. Ideas were summarized to learn the experiences the COVID-19 testing exercises. Lesson Learned: This is a huge experience for Haramaya University to participate in the national call to increase the testing platform in the management of COVID19. Close work relationship with the public health authorities at all levels demonstrated the university's commitment to public service. The university has used the opportunity to advance its molecular testing capability by training its staff and students. The University has also contributed to the capacity development for laboratories in the surrounding areas of Harar, Somali, Oromia, and Dire Dawa. The pandemic has been an opportunity in harnessing existing resource for the benefit of the public during such times of dire needs to provide critical public health laboratory interventions.